Characteristics of Star Fruit Extract (Averrhoa Bilimbi Linn) at Ethanol Solvent Treatment and Extraction Temperature - Yemima Maria Lasma Roha Sitompul; Ni Made Wartini; I Made Sugita (International Journal Labs, 2022)
Background: Starfruit is a type of plant that contains a lot of acids. In addition to containing acids, star fruit also contains bioactive compounds such as polyphenols, flavonoids, alkaloids, saponins, and tannins that have the potential to inhibit bacterial activity. Objective: This study aims to determine the effect of ethanol solvent concentration and extraction temperature on the characteristics of star fruit extract, to determine the ethanol solvent concentration and the best extraction temperature to produce star fruit extract. Method: The experiment conducted was a factorial experiment with two factors designed using a Randomized Design Group (RAK). The factor I is the concentration of ethanol solvents which consists of two types, namely 96% ethanol and 70% ethanol. Factor II is the extraction temperature consisting of 3 types, namely 30oC, 40oC, and 50oC. The data were analyzed using variance analysis and further tested with Honest Real Differences. Results: The results showed that ethanol solvent concentration and extraction temperature and their interactions affected the amendment, total flavonoids, total tannins, and total acids. The highest yield, total flavonoids, tannins and acids were shown at the treatment with an ethanol concentration of 96% and an extraction temperature of 30°C. Conclusion: The conclusion of this study is that the treatment with an ethanol solvent concentration of 96% and an extraction temperature of 30 °C is the best treatment to obtain star fruit extract with yield characteristics of 71%, total flavonoids of 7.10%, tannins total 0.914 mg QE /g, and total acid 34.24%.